Dehydratation und Alkoholwirkung als kombinierte Ursachen eines akuten Delirs = Dehydration and the effect of alcohol as a combined cause of acute delirium - Dettling, Andrea; Skopp, Gisela; Haffner, Hans-Thomas (Rechtsmedizin, 2016)
We report a 37-year-old man who attracted attention on a hot summer’s day by experiencing acute delirium. Back-extrapolation of his blood alcohol concentration from the time of sampling to the time of the incidence of a maximum of 1.11 permille could not explain his psychopathological appearance. Other commonly abused drugs were ruled out. The psychiatric history and clinical findings were normal. His condition rapidly returned to normal after he had been taken to a cool environment and had ingested 2 L of fluid. Recovery conditions support the conclusion of dehydration as the cause of the delirium, probably associated with a mild to moderate influence of alcohol.